Anxiety disorders in old age: psychiatric comorbidities, quality of life, and prevalence according to age, gender, and country - Canuto, Alessandra; Volkert, Jana (American journal of geriatric psychiatry, 2018)
Objectives Previous estimates of the prevalence of anxiety disorders in late life vary greatly due to the lack of reliable diagnostic tools. This MentDis_ICF65+ study assessed 12-month prevalence rates of anxiety disorders and age- and gender-related differences in comorbidities, as well as impact on quality of life.The study used a cross-sectional multicenter survey.Participants.The study sample comprised 3,142 men and women aged 65 to 84 years, living in five European countries and Israel.MeasurementsAnxiety disorders were assessed using computer-assisted face-to-face interviews with an age-appropriate diagnostic interview (CIDI65+).Results The prevalence of anxiety disorders was 17.2%. Agoraphobia was the most frequent disorder (4.9%), followed by panic disorder (3.8%), animal phobia (3.5%), general anxiety disorder (3.1%), post-traumatic stress disorder (1.4%), social phobia (1.3%), and obsessive-compulsive disorder (0.8%). The prevalence rate of any anxiety disorder dropped by 40% to 47% in adults aged 75-84 years compared with those aged 65-74 years. Women were twice as likely to present with agoraphobia or general anxiety disorder as men. Only panic disorder and phobia were associated with comorbid major depression. The negative relationship with quality of life was limited to agoraphobia and generalized anxiety disorder.Conclusions.The age-appropriate CIDI65+ led to higher prevalence rates of anxiety disorders in the elderly, yet to weaker associations with comorbidities and impaired quality of life compared with previous studies.
Gesehen am 16.04.2018